2012
DOI: 10.1371/journal.pone.0047575
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease and Atrial Fibrillation: A Nationwide Population-Based Study

Abstract: ObjectivesPrecise mechanisms of atrial fibrillation (AF) are uncertain, but their association with esophageal disorders has been recently proposed. The association between gastroesophageal reflux disease (GERD), the most common gastroesophageal disorder, and AF remains undetermined. We therefore aimed to investigate the association between GERD and later development of AF.Methods and ResultsPatients with GERD were identified from the 1,000,000-person cohort dataset sampled from the Taiwan National Health Insur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 38 publications
2
47
0
6
Order By: Relevance
“…The relationship between GERD and cancers of the hypopharynx and oropharynx remains far from established [8,10]. This study succeeded in identifying a link between these two entities; however, our results should be interpreted in light of a limitation common to nationwide population-based studies [3,14,[17][18][19]21,22], namely a lack of information related to carcinogen exposure history (e.g., smoking habits, alcohol consumption, and infection with human papillomavirus) in the dataset. This makes it premature to infer a causal link between GERD and HNCs in either direction, or whether a confounding factor might account for both findings.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The relationship between GERD and cancers of the hypopharynx and oropharynx remains far from established [8,10]. This study succeeded in identifying a link between these two entities; however, our results should be interpreted in light of a limitation common to nationwide population-based studies [3,14,[17][18][19]21,22], namely a lack of information related to carcinogen exposure history (e.g., smoking habits, alcohol consumption, and infection with human papillomavirus) in the dataset. This makes it premature to infer a causal link between GERD and HNCs in either direction, or whether a confounding factor might account for both findings.…”
Section: Discussionmentioning
confidence: 84%
“…The validity of findings from this large-scale nationwide survey is increased through the minimization of selection bias and complete follow-up of cases. Recall bias was avoided by using a recorded history of GERD, which requires diagnostic evidence of either endoscopy or 24-h pH-meter inspection prior to treatment with proton pump inhibitors [14][15][16]. Furthermore, data regarding cancer diagnosis can be regarded as exhaustive and reliable because it was linked to the Catastrophic Illness Registry, which requires histopathologic proof of malignancy before certification [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastroesophageal reflux disease (GERD) is the most common gastrointestinal diagnosis made during visits to outpatient clinics [1,2]. A potential association between GERD and atrial fibrillation (AF) development has been proposed in previous studies, mainly attributed to the close positioning of the esophagus and the left atrium [1,2].…”
Section: To the Editormentioning
confidence: 99%
“…A potential association between GERD and atrial fibrillation (AF) development has been proposed in previous studies, mainly attributed to the close positioning of the esophagus and the left atrium [1,2]. Previous studies have demonstrated a high incidence of pathologic reflux following left atrial (LA) ablation [3,4].…”
Section: To the Editormentioning
confidence: 99%